Pendampingan Masyarakat melalui Penerapan Mesin Pengepres Baglog Jamur: Studi Pemberdayaan Usaha Jamur di Desa Lau Bakeri Kabupaten Deli Serdang - Tarigan, Efrata; Siahaan, Sihar (Yayasan Pendidikan Intan Cendekia, 2023)
Lau Bakeri Village is one of the villages in Kutalimbaru District, Deli Serdang Regency, where 30 families of them run a business of oyster mushroom cultivation according to the humidity in the area. The service partners have been running the oyster mushroom cultivation business for 10 years, most of which are still done manually, including compaction of planting media (baglog) which takes a long time and requires hired workers with a salary of Rp. 200,000, - per day. The demand for mushrooms is still quite open, but due to limited land and labor, not all of them can be served. Making baglog pressing machines and training on the use of machines are expected to be solutions that can overcome problems for oyster mushroom cultivators. At the time of giving the tools and socializing the use of this mushroom baglog pressing machine, the community was very welcoming, and hoped that this community service partnership like this would continue